Visuomotor mechanisms in reaching in adults, infants, and children - Babinsky, E (2009)
This thesis investigates how adults, infants, and children use visual information to control reaching movements. To do this, the kinematics of a reaching movement were recorded using a 6 camera motion tracking system. Adult reaching movements were investigated in three different experiments. The first experiment looked at the effect of visual information about the reach space and the target on reaching movements. Adult reaches are significantly affected by removal of visual information about the reach space and the target, e.g. peak speed decreases as distance information is occluded. Adult reaching movements are also affected by the length of the delay between viewing an object and then reaching for it in complete darkness. Experiment 2 reveals that there is a linear increase in movement duration, decrease in peak speed, and increase in maximum grip aperture with increasing temporal delay. This is due to the decay of dorsal visual information. Experiment 3 found that a cautious reaching movement can be defined as a reach where duration increases, average speed decreases, and peak timing is proportionally earlier in the reach. The three developmental experiments investigated the changes in reaching in infancy, in typically developing 5-year-old children, and in children with Williams syndrome (WS). Between 9 and 16 months of age, infants develop better coordination of reaching movements. Improved dark reaching behaviour in 16-month-olds may be associated with more mature processing in the dorsal visual stream. Reaching movements in 5-year-old children are straighter and faster than infant reaches but behaviour is not yet stereotyped like adults. WS children generate reaches that are slower and incorporate more movement units than 5-year-old children, and WS behaviour may reflect poor processing of dorsal visual information rather than poor control of arm movement.